2006
DOI: 10.1177/0146167206288669
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal and Noninterpersonal Interactions, Interpersonal Motives, and the Effect of Frustrated Motives

Abstract: A new circumplex model of interpersonal interaction emphasizes the motives that drive interpersonal behaviors and the negative affect (such as anger) that occurs when a strongly activated motive is frustrated. This study examined the model experimentally by varying conditions designed to activate and frustrate interpersonal motives. One hundred twenty-nine students engaged in text-based discussions using a computer. Three factors were varied: (a) activation of interpersonal motives--participants believed the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 21 publications
1
37
1
Order By: Relevance
“…Consistent with this line of thought, Tiedens (2001) found that a person who expresses anger is accorded greater status by observers. Schectman and Horowitz (2006) found that assertive people who believed themselves to be interacting with a dominating partner expressed anger in response. In short, we do not see a great deal of difficulty in pointing to desired conditions that are sometimes disrupted or interfered with, resulting in anger (see also Frijda, 2007, …”
Section: Approach Motive As Precondition To or Consequent To Angermentioning
confidence: 99%
“…Consistent with this line of thought, Tiedens (2001) found that a person who expresses anger is accorded greater status by observers. Schectman and Horowitz (2006) found that assertive people who believed themselves to be interacting with a dominating partner expressed anger in response. In short, we do not see a great deal of difficulty in pointing to desired conditions that are sometimes disrupted or interfered with, resulting in anger (see also Frijda, 2007, …”
Section: Approach Motive As Precondition To or Consequent To Angermentioning
confidence: 99%
“…In other words, friendly behavior begets friendly behavior and hostile behavior invokes hostile behavior, but dominant behavior is more likely to invite submissive behavior. In addition, interpersonal complementarity (i.e., "sameness on the affiliation dimension and oppositeness on the dominance dimension"; Sadler and colleagues, 2011, p. 126) leads to more satisfying and harmonious relationships (Dryer & Horowitz, 1997;Kiesler, 1996;Shechtman & Horowitz, 2006). For example, in a laboratory experiment, participants were more satisfied when they were paired with an experimental confederate who expressed dominance levels opposing their own expressed dominance goals (Dryer & Horowitz, 1997).…”
Section: Narcissism and Leadershipmentioning
confidence: 99%
“…For example, in a laboratory experiment, participants were more satisfied when they were paired with an experimental confederate who expressed dominance levels opposing their own expressed dominance goals (Dryer & Horowitz, 1997). Similarly, when dominant participants were paired with highly dominant partners, the participants expressed increased anger toward their partners (Shechtman & Horowitz, 2006).…”
Section: Narcissism and Leadershipmentioning
confidence: 99%
“…[16]) to understand robots as social actors. However, Brennan [3], Amalberti et al [1], Fischer [8] and Shechtman & Horrowitz [22] report on considerable differences between speech to computers and speech to other humans even in speech-based computer systems, and Fischer [7] demonstrates considerable interpersonal variation in understanding robots as social actors. Whether language use has a systematic impact on people's understanding of the robot's actions as intentional and on their willingness to assist the robot is thus open.…”
Section: Related Workmentioning
confidence: 99%